2008
DOI: 10.1038/bjp.2008.318
|View full text |Cite
|
Sign up to set email alerts
|

Native profiles of α1A‐adrenoceptor phenotypes in rabbit prostate

Abstract: Background and purpose: a 1 -Adrenoceptors in the rabbit prostate have been studied because of their controversial pharmacological profiles in functional and radioligand binding studies. The purpose of the present study is to determine the native profiles of a 1 -adrenoceptor phenotypes and to clarify their relationship. 3 H]-silodosin in intact segments were composed of a 1L phenotype with low affinities for prazosin (pKi ¼ 7.1), 5-methyurapidil and N-[2-(2-cyclopropylmethoxyphenoxy)ethyl]-5-chloro-a,a-dimeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 29 publications
(66 reference statements)
2
35
0
Order By: Relevance
“…3 H]-prazosin at subnanomolar concentrations cannot bind sufficiently to a1L-adrenoceptors (Su et al, 2008;Muramatsu et al, 2009). Silodosin and its tritiated radioligand are known to be of equally high affinity for both the a1A-and a1L-adrenoceptors Su et al, 2008) (Table 2).…”
Section: Binding Assay With Whole Cells and Intact Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 H]-prazosin at subnanomolar concentrations cannot bind sufficiently to a1L-adrenoceptors (Su et al, 2008;Muramatsu et al, 2009). Silodosin and its tritiated radioligand are known to be of equally high affinity for both the a1A-and a1L-adrenoceptors Su et al, 2008) (Table 2).…”
Section: Binding Assay With Whole Cells and Intact Tissuesmentioning
confidence: 99%
“…Silodosin and its tritiated radioligand are known to be of equally high affinity for both the a1A-and a1L-adrenoceptors Su et al, 2008) (Table 2).…”
Section: Binding Assay With Whole Cells and Intact Tissuesmentioning
confidence: 99%
“…A binding assay that uses intact tissue segments has been shown to be a powerful method for analysis of the intrinsic properties of receptors present in native tissues (Muramatsu et al, 2005Anisuzzaman et al, 2008a;Sathi et al, 2008;Su et al, 2008). When using the intact segment binding assay, in contrast to conventional membrane binding assays, it is not necessary to consider either the change of receptor characteristics that may occur upon tissue homogenization that eliminates the receptor's natural environment or the selective loss of receptors upon isolating membranes by differential centrifugation (Muramatsu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These lines of evidence suggest that the pharmacological profile of β 1L -adrenoceptor can not be interpreted by a simple conformational change or allosteric state in the β 1 -adrenoceptor molecule. In this context, it is interesting to note recent reports that receptors can have distinct phenotypes even though the origin is the same receptor gene (4,5,24,25). Recently, we have demonstrated that the α 1L -adrenoceptor is derived from the α 1A -adrenoceptor gene but is a distinct phenotype from the classical α 1A -adrenoceptor (25,26).…”
Section: Discussionmentioning
confidence: 87%